Improving Students' Speaking Skills Through English Songs and Puppets at Second Grade of SMKN 1 Logas Tanah Darat in The Academic Year Of 2022/2023 - Fitri Susanti; Amelia Rinanda; Dewi Yupita Sinaga (LPPI Yayasan Almahmudi bin Dahlan, 2023)
The study aims at improving the speaking skill of the students at second Grade of SMKN 1 Logas Tanah Darat in the academic year of 2022/2023. The English songs and puppets were chosen as the teaching media in this study. This study was action research consisting two cycles. The research was carried out at the second semester from April to May 2023. It involved the researcher, the collaborator, and the students. The participants of this research were 23 students of At second Grade of SMKN 1 Logas Tanah Darat in the academic year of 2022/2023. The data of this study were qualitative and quantitative. The qualitative data were obtained by observing teaching and learning process during the implementation of the actions and interviewing. It was in the form of field notes and interview transcripts. The quantitative data were taken by assessing the student’s speaking skill through the pre-test and the post-test. The finding of the first cycle indicated that the students’ speaking skill and involvement improved along with a lot of speaking practices. The result of the second cycle shows that the implementation of English songs and puppets improved the students’ speaking skill, especially their accuracy and interest by providing them with various topics, songs, and activities. It was also found that using the language more often can improve their fluency. The indicators of the success of the implementation were that: (1) Students were more motivated in learning English and to be involved in speaking activities; (2) Students were actively answer the question and give comment; (3) Students were more active in the speaking activities during the teaching and learning process, and (4) There were many kinds of activities in every meeting, and also pictures that make the students feel interested to do the activities. Furthermore, the findings were also supported by the means of the students’ speaking score which had improved from 6.2 in the pre-test and to 7.3 in the post-test. Keywords: Students' Speaking Skills, English Songs and Puppets, classroom action research